HTML, XHTML, & CSS all-in-one for dummies - Harris, Andrew , 1964- (Hoboken, New Jersey : Wiley Publishing ; Chichester, West Sussex : John Wiley [distributor], 2011)
A complete and fully updated reference for these key Web technologies HTML, XHTML, and CSS are essential tools for creating dynamic Web sites. This friendly, all-in-one guide covers what programmers need to know about each of the technologies and how to use them together
1. Creating the HTMLIXHTML foundation -- 2. Styling with CSS -- 3. Using positional CSS -- 4. Client side programming with JavaScript -- 5. Server programming with PHP -- 6. Managing with My SOL -- 7. Into the future with AJAX -- 8. Moving from pages to sites
"Covers HTML5 and prior versions of HTML" -- p. [1] of cover
Includes index
Previous ed.: published as HTML, XHTML, and CSS all-in-one desk reference for dummies by Andy Harris and Chris McCulloh. 2008
Keywords: Cascading style sheets; HTML (Document markup language); XHTML (Document markup language)